Prophetic Parenting Skills of Generation Z Parents in Educating Children in the Digital Era - Khoirunnisa, Aisyah Naila; M. Suud, Fitriah (Jurnal Pendidikan Islam, 2025)
The digital era brings new challenges in parenting, especially for Generation Z parents who have grown up with technology since a young age. This study aims to identify and explore the application of prophetic parenting skills by Generation Z parents in educating their children amid the tide of digitalization. This study uses a descriptive qualitative approach with a case study method, involving seven parents aged 23–28 who have children ranging from toddlers to elementary school age. Data were collected through an online questionnaire and analyzed descriptively. The results show that the parenting strategies applied include early religious habits, instilling the values of monotheism and morals, role modeling, warm Islamic communication, strengthening digital etiquette, and a loving approach. Despite challenges such as gadget addiction, differences in environmental values, and limited digital literacy, the application of prophetic parenting has proven to have a positive impact on children's spiritual, moral, and social development. These findings confirm that prophetic parenting is a relevant and applicable approach in shaping children's character in the digital age.